Gambaran Kasus Parotitis Anak Sekolah Dasar di Wilayah Kerja Puskesmas Loa Bakung - Pakki, Irfansyah Baharuddin; Herliani, Resda; Noorhayaty, Noorhayaty; Insany, Vicca Yulia; Yuniasih, Arista Dian; Sigit, Ratih Fianni (UI Scholars Hub, 2025)
Parotitis is a disease caused by mumps virus infection. The infection attacks the parotid glands, causing symptoms such as fever, swelling on the side of the face accompanied by pain. Data from the Samarinda City Health Office shows that there were 380 cases of mumps from September to early October 2024. The increase in cases also occurred among elementary school children, but there is no definitive data yet that illustrates the number and distribution of parotitis cases. The aim of this study is to identify the risk factors for mumps in elementary school children in the Loa Bakung working area. This study is a descriptive study. The sample was 5154 students. Data collection was done by distributing questionnaires online in the form of Google Forms and interviews to teachers during field visits. The number of schools that filled out the Google form was 11 schools (91.7%), and the number of classes that filled out the Google form was 55 classes (31.9%). Analysis was conducted on the incidence data of cases, patient characteristics, and school intervention efforts. The study showed the incidence of mumps cases among 238 students, with the highest number at SD Muhammadiyah 5 (37.82%) and the highest attack rate at MI Tijanul Jawahir (13.89%). The majority of the patients were 9 years old (27.94%) and male (53.36%). The main symptoms experienced are swelling in the cheeks (85.5%) and fever (67.3%). The preventive measures taken by the school include the use of masks, provision of handwashing facilities, and granting dispensations. The incidence of mumps cases shows a significant increase in the elementary school environment. Further investigation is needed regarding the factors influencing the high attack rate and prevention strategies. Keywords : Parotitis, attack rate, elementary school, prevention, Samarinda